Multimodal Analgesia Techniques within Enhanced Recovery After Cesarean Surgery (ERACS) and Their Effect on Early Mobilisation and Breastfeeding After Caesarean Section: A Systematic Review of Randomised Controlled Trials and Primary Studies - Ilham Ghifari; Michael Yazid Raushan Dhamir; Sabran Jamil Pulubuhu; Rizki Syafira (The Indonesian Journal of General Medicine, 2026)
Introduction: Caesarean section is the most frequently performed inpatient surgical procedure globally, generating moderate-to-severe somatic and visceral pain that impedes early mobilisation and lactation initiation. Enhanced Recovery After Cesarean Surgery (ERACS) positions opioid-sparing multimodal analgesia as the key pharmacological component. This systematic review aimed to synthesise randomised controlled trial evidence on the effect of multimodal analgesic techniques within an ERACS framework on early mobilisation and breastfeeding success after caesarean delivery. Methods: This systematic review adhered to PRISMA 2020 guidelines. Inclusion criteria: randomised controlled trials in women undergoing caesarean delivery comparing a multimodal/ERACS-embedded analgesic strategy with active or placebo comparator, reporting at least one of sixteen pre-specified outcome domains. Risk of bias was assessed using Cochrane RoB 2. Certainty of evidence was evaluated using GRADE. Synthesis was performed narratively-structurally with vote-counting of effect direction. Results: Twenty-eight randomised controlled trials (approximately 2,900 parturients) from 14 countries were included. Movement-evoked pain at 24 hours was significantly reduced by fascial plane blocks when neuraxial morphine was absent; opioid-sparing of 40-73% was achieved in morphine-free regimens. Early mobilisation improved significantly: full mobilisation on postoperative day 1 was achieved by 98% of women receiving multimodal regimens versus 83% receiving placebo and 58% receiving standard care. Breastfeeding at discharge increased from 48.3% to 67.2% under an ERACS pathway (p=0.046). Quality of recovery, satisfaction, pruritus, nausea and vomiting, bowel function, catheter removal, and length of stay all favoured optimised multimodal regimens. Adding fascial plane blocks to regimens already containing intrathecal morphine conferred no additional benefit beyond six hours. Discussion: An analgesic ceiling effect exists in which the contribution of any single modality is conditional on the background regimen. Intrathecal morphine remains the reference standard; when unavailable, fascial plane blocks deliver clinically important opioid-sparing translating into earlier ambulation. ERACS benefits on mobilisation and lactation appear to be mediated more by reduction of opioid-related adverse effects than by absolute pain score reduction. Conclusion: Multimodal, opioid-sparing analgesia delivered within an ERACS pathway produces statistically significant and clinically meaningful improvements in movement-evoked pain, opioid consumption, early mobilisation, quality of recovery, length of stay, and in-hospital breastfeeding after caesarean section. Regimen design should be stratified by whether long-acting neuraxial opioid is used. Future trials should adopt the ERACS core outcome set.